Dietary supplementation effects of Chlorella vulgaris on performances, oxidative stress status and antioxidant enzymes activities of prepubertal New Zealand White rabbits - Sikiru, A. B. (2021)
Dietary supplementation of the microalgae significantly increased the rabbits’ growth weights (p < 0.01) without significant increase or reduction in feed intakes (p < 0.56), but significantly enhanced feed to gain ratio. The microalgae supplementation significantly protected the rabbits against oxidative stress damages through the reduction of malondialdehyde concentrations (p < 0.001) and increased total antioxidant capacity (p < 0.003). It also led to higher superoxide dismutase activity (p < 0.001), increased catalase activity (p < 0.003), and higher concentration of reduced glutathione (p < 0.001).